The Extent of the Affection of Some Factors on the Responsibility of External Auditor for Detection and Reporting Fraud Operations: An Empirical Study in the Kingdom of Saudi Arabia - Alrefai, Bdour Saeed (Journal of Economic, Administrative and Legal Sciences, 2025)
This research aims to study the extent of the affection of some factors on the responsibility of the External Auditor on the detection of fraud operations and reporting them.In order to achieve this objective the study is divided into two main parts: in the first part the theoretical side is addressed by reviewing the related literature, where as the second part included designing of the questionnaire form which includes the factors affecting the external auditor's responsibility in discovering fraud operations and reporting them and which are used to deal with all the thesis of the study. After distributing the questionnaire to the two categories of the study, it is collected and analyzed statistically with a view to determine the extent of the affection of some factors on the external auditor's responsibility in discovering fraud operations and reporting them. The result of the study indicated that there is considerable conformity between individuals of the study sample (auditing firms, and beneficiaries of published financial statements and reports) about along number of factors which may affect the external auditors' responsibility in discovering fraud operations and reporting them; where as there is a big difference in the viewpoint of study simple on both categories about a number of factors with regard to the affect of these factors on the responsibility of the external auditor in discovering fraud operations and reporting them. The study concluded by presenting a number of recommendations, the most important of which is setting a general frame for the factors affecting the responsibility of the external auditor in discovering cases of fraud and reporting them. This should not only be based on the viewpoint of a certain category, but of several categories in order to lessen the risks that the external auditor losing that trust of the beneficiaries of financial statements and reports; thus, providing a suitable work environment for the external auditor during auditing operations free of pressure from colleagues or the office owner or the client and his employees usually faced by the auditor. In so doing suitable environment is created for achieving the required quality for the auditing profession.
Keywords: Fraud operations; external auditor; external auditor report